THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND PREGNANT WOMEN'S BEHAVIOR IN EFFORT PREVENT ANEMIA - Sulpat, Emuliana; Bella Nurramdhani, Putri; Mardhika, Amellia; Fadliyah, Lailatul; Harianto, Susilo; Pangestu Mei Tyas, Anestasia (Universitas Airlangga, 2024)
Introduction: Anemia experienced by pregnant women will hurt the baby, namely the risk of premature birth, low birth weight, and an increased risk of perinatal death. This study aims to determine the relationship between family support and the behavior of pregnant women in efforts to prevent anemia. Methods: This study used analytical research with a cross-sectional approach, the population in this study was all pregnant women in Madiun. This study used purposive sampling techniques. The sample used in this study was 112 respondents. To find out the relationship between variables in this study, the Chi-Square statistical test was used with the result that if the p-value is 0.05, it means that there is a significant relationship between the two variables. Results: The results of the study using the Chi-Square correlation test showed that the Fischer Exact Test value was 0.001. Because the Chi-Square test value is 0.001 < 0.005, it can be concluded that there is a relationship between family support and the behavior of pregnant women in efforts to prevent anemia. Conclusions: Families are expected to always provide motivation, help, and accompany pregnant women so that pregnant women feel safe, comfortable, and calm.